PENGGUNAAN INSEKTISIDA RUMAH TANGGA ANTINYAMUK DI DESA PANGANDARAN, KABUPATEN PANGANDARAN - Nurul Hidayati Kusumastuti (Pusbindiklat - LIPI, 2014)
There are many kinds of house insecticide used as antimosquito insecticide. An unsafe application of it might affect our health. Pangandaran Village is a malaria and dengue hemorrhagic fever (DHF) in the district of Pangandaran, West Java. The aim of this study is to describe the use of house insecticide by many households in Pangandaran village. An exploratory study with cross-sectional design is conducted for four months starting from April 2014. Several interviews were randomly assigned to 201 households to discover the use of house antimosquito insecticide. Sample collecting method is done using multiple random sampling over each subvillage. The numbers of household interviewed are determined by the proportion number of household in each neighborhood unit (RT). There are 82% households using antimosquito for more than ten years (59%) and using repellent daily (19.4%). Comfort is the main reason why most households use antimosquitos (46%). Households use insecticides one time at night (79.6%) and spend less than IDR 5,000 to buy insecticide. This study provides supporting information for local stakeholders over the use of house insecticide that can be benefitted as a reference for developing policy on vector control disease.